1990
DOI: 10.1021/bi00481a005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a light-induced pH gradient on purple-to-blue and purple-to-red transitions of bacteriorhodopsin

Abstract: Bacteriorhodopsin-containing vesicles that were able to alkalize the extravesicular medium by greater than 1.5 pH units under illumination, i.e., inside-out vesicles, were reconstituted by reverse-phase evaporation with Halobacterium halobium polar lipids or exogenous phospholipids. Acid titration of a dark-adapted sample was accompanied by a color change from purple to blue (pKa = 2.5-4.5 in 0.15 M K2SO4), and alkali titration resulted in the formation of a red species absorbing maximally at 480 nm (pKa = 7 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 60 publications
1
11
1
Order By: Relevance
“…Apparently, the long-lived O intermediate may be formed both from the trans-bR and 13-cis-bR molecules. This contradicts the conclusion of Nasuda-Koyuama et al [12] that only 13-cis-bR is able to give the bathoform in response to low pH in the intravesicular volume.…”
Section: Resultscontrasting
confidence: 76%
See 2 more Smart Citations
“…Apparently, the long-lived O intermediate may be formed both from the trans-bR and 13-cis-bR molecules. This contradicts the conclusion of Nasuda-Koyuama et al [12] that only 13-cis-bR is able to give the bathoform in response to low pH in the intravesicular volume.…”
Section: Resultscontrasting
confidence: 76%
“…Thus, the above data indicate that the membrane potential is the main cause for the flash‐induced formation of the long‐lived intermediate. However, they cannot exclude that its formation under continuous illumination may also be caused by acidification of the intravesicular volume as was suggested by Nasuda‐Koyuama et al [12]. It is noteworthy that light adaptation increases the magnitude of the O intermediate concurrently with the increase in the M intermediate magnitude (data not shown).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…In fact, the lipid component (for example triglycolipid) observed in the P622 crystal is partially removed or missing in other crystal forms. It has been reported that the neutral purple form is destabilized in bR-containing vesicles reconstituted with egg lethicin, in which the transition from the neutral purple form into an inactive red form with max at 480 nm takes place at pH 6.5 (Nasuda- Kouyama et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…32 In the monomeric state, on the other hand, the neutral purple conformation is stable in a very restricted range of pH; i.e., the acid blue transition and the alkaline red transition are observed at pH ∼ 4 and ∼ 7, respectively, when bR monomers are incorporated into vesicles composed of egg phosphatidyl choline. 43 These observations suggest that trimerization is effective in maximizing the proton pumping power, which is defined by the largest pH gradient that the proton pump can generate across the membrane. For halobacteria living in alkaline lakes, however, generation of a large pH gradient (i.e., alkalization of the cytosol) may be harmful.…”
Section: Discussionmentioning
confidence: 99%